Low-melting-point aluminum alloy flux-cored wire flux and preparation method thereof

CN122683354BActive Publication Date: 2026-10-23SHANDONG SHISHANG WELDING MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611184651.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-23
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

[0006]在铝锡体系中,锡与铝的密度、熔点差异大,常规粉料混合易产生组分偏析;堆焊时铝表面致密氧化膜难以破除,导致堆焊层与钢背基体结合强度不足,受异质材料物理行为差异及界面反应条件制约,简单提高热输入或延长保温时间虽可改善结合,却易引起晶粒粗化、熔蚀等副作用,无法同时满足高结合强度与组织细化的要求

Benefits of technology

1、本发明通过CsF-AlF3低共晶钎剂体系与Bi元素的协同降熔作用,实现药粉熔化温度的精准调控,将起始熔化温度稳定在480℃左右,较传统Nocolok钎剂大幅降低。低温钎焊特性可显著降低母材热输入、减小热变形与晶粒粗化风险,尤其适配铝合金精密构件、热敏组件的低温连接场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a low-melting-point aluminum alloy flux-cored wire flux powder and a preparation method thereof, and belongs to the technical field of welding wire flux powder. First, an Al-Si-Cu-Mg-Bi-Sr alloy is atomized by inert gas to obtain alloy powder; then, a fluoride compound system is atomized to obtain brazing powder, and the brazing powder is mixed with lithium chloride-sodium chloride mixed salt powder, and then the mixture is granulated by a composite solution and heat-treated to obtain composite brazing powder; finally, the alloy powder and the composite brazing powder are mixed in proportion to obtain the low-melting-point aluminum alloy flux-cored wire flux powder. Through the synergistic melting reduction effect of the CsF-AlF3 low-eutectic brazing agent system and the Bi element, the melting temperature of the flux powder is accurately controlled, and the initial melting temperature is stably kept at about 480 DEG C, which is greatly reduced compared with traditional brazing agents. The low-temperature brazing characteristics can significantly reduce the heat input of the base material, reduce the risk of thermal deformation and grain coarsening, and are especially suitable for low-temperature connection scenes of aluminum alloy precision components and heat-sensitive components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of welding wire flux technology, specifically to a low-melting-point aluminum alloy flux-cored welding wire flux and its preparation method. Background Technology

[0002] Aluminum-based flux-cored welding wire, with its advantages of adjustable composition and wide process adaptability, is widely used in aluminum alloy brazing, light alloy surface cladding, and precision structural connection scenarios, and is one of the core welding material categories in the advanced manufacturing field.

[0003] Aluminum-based alloy powders are mostly produced using water atomization processes. Due to aluminum's strong affinity for oxygen, the oxygen content of the powder is relatively high. This exacerbates interfacial oxidation during subsequent pressing and high-temperature extrusion, leading to defects and reduced density in the welding wire, thus affecting welding reliability. Due to the thermodynamic limitations of oxidation in the aluminum-water system, adjusting parameters such as water temperature and pressure cannot completely solve the problem. Inert gas atomization must be used to achieve a qualitative improvement.

[0004] Fluoride fluxes are traditionally prepared through physical and mechanical mixing, which cannot achieve molecular-level uniformity. This results in deviations in actual composition and melting points from the target value, narrowing the soldering temperature window and reducing process tolerance. The statistical limitations of physical mixing mean that extending the mixing time or changing the fineness of the powder cannot solve this problem. Chemical synthesis is necessary to precisely control the composition from the source. However, chemical synthesis routes place higher demands on process continuity and batch stability.

[0005] To improve welding efficiency or achieve special functions (such as aluminum-tin cladding), it is often necessary to significantly increase the filling rate of the active component in the flux core. However, a high filling rate significantly alters the plasticity and rheological properties of the welding wire, making conventional drawing and rolling impossible; conversely, reducing the filling rate limits metallurgical functionality. This conflict cannot be resolved by adjusting the number of drawing passes or lubrication conditions, as the deformation behavior of the composite material formed by the metal outer layer and powder is fundamentally different from that of a single metal.

[0006] In the aluminum-tin system, tin and aluminum have large differences in density and melting point, and conventional powder mixing is prone to component segregation. During welding, the dense oxide film on the aluminum surface is difficult to remove, resulting in insufficient bonding strength between the weld layer and the steel backing substrate. Due to the differences in physical behavior of heterogeneous materials and the interface reaction conditions, simply increasing the heat input or extending the holding time can improve the bonding, but it is easy to cause side effects such as grain coarsening and erosion, and cannot simultaneously meet the requirements of high bonding strength and fine microstructure.

[0007] Based on this, the present invention designs a low-melting-point aluminum alloy flux-cored welding wire powder and its preparation method to solve the above problems. Summary of the Invention

[0008] To address the aforementioned shortcomings of existing technologies, this invention provides a method for preparing low-melting-point aluminum alloy flux-cored welding wire powder, comprising the following steps: S1: The alloy powder is prepared by mass percentage of 7.5-12.5% ​​Si, 3.0-6.0% Cu, 0.1-0.5% Mg, 0.01-0.2% Bi, 0.01-0.05% Sr, with the balance being Al. After melting at 710-760℃, the alloy powder is prepared by inert gas atomization powder preparation process. S2: Potassium fluoride and aluminum fluoride are compounded to obtain mixture A, and cesium fluoride and aluminum fluoride are compounded to obtain mixture B. Mixture A and mixture B are combined at a mass ratio of 90-96:4-10 to obtain a combined material; the combined material is then atomized with inert gas to obtain brazing powder. S3: Weigh 14.5-16.5% lithium chloride and 28-31% sodium chloride by mass ratio, heat and melt them in a nitrogen atmosphere, and then atomize them with an inert gas to obtain mixed salt powder; S4: Weigh out 50-56:44-50 of brazing powder and mixed salt powder by mass ratio and mix them. Spray the mixture into the composite solution and stir. Then treat it in a nitrogen atmosphere at 200-350℃ for 1-3 hours. After cooling, the composite brazing powder is obtained. S5: Mix the alloy powder and composite brazing powder at a dry weight ratio of 60-75:25-40 to obtain low melting point aluminum alloy flux-cored welding wire powder.

[0009] Furthermore, S1 is specifically composed of 7.5-12.5% ​​Si, 3.0-6.0% Cu, 0.1-0.5% Mg, 0.01-0.2% Bi, and 0.01-0.05% Sr by mass percentage, with the balance being Al. It is melted at 710-760℃ and transferred to a sealed holding furnace. The powder is then atomized using an inert gas atomization process with argon as the atomizing medium at 1.5-3.0 MPa. After atomization, the powder is classified by cyclone and collected to obtain alloy powder of 45-150 μm.

[0010] Furthermore, S2 specifically involves: mixing potassium fluoride and aluminum fluoride in a molar ratio of 1:1 to obtain mixture A; mixing cesium fluoride and aluminum fluoride in a molar ratio of 1:1 to obtain mixture B; combining mixture A and mixture B at a mass ratio of 90-96:4-10 to obtain a combined material; holding the combined material at 680-750℃ for 30-60 minutes in an argon atmosphere; then atomizing the material using an inert gas atomization process at 1.0-2.5MPa in an argon atmosphere; cooling and collecting the material in stages to obtain 5-15μm powder to obtain brazing powder.

[0011] Furthermore, in S2, when weighing potassium fluoride, aluminum fluoride, and cesium fluoride, 0.5-2% of their respective weights are added to compensate for the volatilization loss during the smelting process.

[0012] Furthermore, S3 specifically involves: weighing 14.5-16.5% lithium chloride and 28-31% sodium chloride by mass ratio, melting them in a nitrogen atmosphere at 580-630℃ for 30-45 minutes, and then atomizing them using an inert gas atomization process at 1.0-2.5MPa in a nitrogen atmosphere. The resulting powder is then cooled and sieved in a dry environment at room temperature and a dew point ≤-40℃, collecting powder with a particle size of 45-75μm to obtain mixed salt powder, which is immediately vacuum-sealed.

[0013] Furthermore, S4 specifically involves: weighing and mixing brazing powder and mixed salt powder in a mass ratio of 50-56:44-50, spraying them into a composite solution containing 0.5-2.0% of their total mass, stirring at 20-40 r / min for 10-30 min, then treating them in a nitrogen atmosphere at 200-350℃ for 1-3 h, and finally obtaining composite brazing powder after cooling.

[0014] Furthermore, in S4, the composite solution is composed of polyethylene glycol and ethanol in a volume ratio of 1:8-15.

[0015] Furthermore, S5 specifically involves mixing alloy powder and composite brazing powder at a dry weight ratio of 60-75:25-40 at 20-60 r / min for 30-60 min to obtain low-melting-point aluminum alloy flux-cored welding wire powder.

[0016] A low-melting-point aluminum alloy flux-cored wire powder prepared according to the method.

[0017] Compared with the prior art, the beneficial effects of this invention are as follows: 1. This invention achieves precise control of the flux melting temperature by leveraging the synergistic melting reduction effect of the CsF-AlF3 hypoeutectic flux system and Bi element, stabilizing the initial melting temperature at around 480℃, a significant reduction compared to traditional Nocolok flux. This low-temperature brazing characteristic significantly reduces heat input to the base material, minimizes thermal deformation and grain coarsening risks, making it particularly suitable for low-temperature connections of precision aluminum alloy components and heat-sensitive assemblies.

[0018] 2. This invention uses an inert gas atomization process to simultaneously prepare alloy powder and flux powder, avoiding the oxidation risk of water atomization process from the source. The oxygen content is stably controlled within 0.2%. The powder has both good flowability and suitable loose / tap density, which is suitable for high-speed continuous powder filling process of flux-cored wire and can also ensure that the powder core is dense and uniform during subsequent drawing and rolling processes, effectively reducing internal defects of the welding wire.

[0019] 3. This invention constructs a fluoride-chloride composite flux, which combines efficient film removal capability with interface activation effect. It can effectively break down the dense oxide film on the surface of the aluminum substrate, significantly improving the spreading wettability and gap-filling ability of the liquid solder. The measured joint tensile strength reaches 168MPa and shear strength reaches 98MPa, with high interfacial bonding strength and good service stability. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0021] Example 1: This example provides a method for preparing low-melting-point aluminum alloy flux-cored welding wire powder, including the following steps: S1: Take 12.5% ​​Si, 6.0% Cu, 0.5% Mg, 0.2% Bi, and 0.05% Sr by mass percentage, with the balance being Al. Melt at 760℃ and transfer to a sealed holding furnace. Atomize using an inert gas atomization process with argon as the atomization medium at 3.0 MPa. After atomization, cyclone classification is performed to collect powder of 45-150 μm to obtain alloy powder with oxygen content ≤0.2%. S2: Potassium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture A, and cesium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture B. Mixture A and mixture B are combined at a mass ratio of 96:10 to obtain a combined material. The combined material is kept at 750℃ for 60 min in an argon atmosphere, and then atomized into powder at 2.5 MPa in an argon atmosphere using an inert gas atomization powdering process. After cooling, the powder is collected in stages, and 5-15 μm powder is obtained to obtain brazing powder. When weighing potassium fluoride, aluminum fluoride, and cesium fluoride, 2% of their respective weight should be added to compensate for volatilization losses during the smelting process; S3: Weigh 16.5% lithium chloride and 31% sodium chloride by mass ratio, melt them at 630℃ for 45 minutes in a nitrogen atmosphere, and then atomize them at 2.5MPa in a nitrogen atmosphere using an inert gas atomization powdering process. The resulting powder is cooled and sieved in a dry environment at room temperature and dew point ≤-40℃. Powder with a particle size of 45-75μm is collected to obtain mixed salt powder, which is immediately vacuum-sealed. S4: Weigh out 56:50 of brazing powder and mixed salt powder by mass ratio and mix them. Spray 2.0% of the total mass of the mixture into a composite solution, stir at 40 r / min for 30 min, then treat at 350℃ in a nitrogen atmosphere for 3 h, and obtain composite brazing powder after cooling. The composite solution is composed of polyethylene glycol and ethanol in a volume ratio of 1:15; S5: Mix the alloy powder and composite brazing powder at a dry weight ratio of 75:40 at 60 r / min for 60 min to obtain low melting point aluminum alloy flux-cored welding wire powder.

[0022] Example 2: This example provides a method for preparing low-melting-point aluminum alloy flux-cored welding wire powder, including the following steps: S1: Take 7.5% Si, 3.0% Cu, 0.1% Mg, 0.01% Bi, and 0.01% Sr by mass percentage, with the balance being Al. Melt at 710℃ and transfer to a sealed holding furnace. Atomize using an inert gas atomization process with argon as the atomization medium at 1.5 MPa. After atomization, cyclone classification is performed to collect powder of 45-150 μm, resulting in alloy powder with an oxygen content ≤0.2%. S2: Potassium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture A, and cesium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture B. Mixture A and mixture B are combined at a mass ratio of 90:4 to obtain a combined material. The combined material is kept at 680℃ for 30 min in an argon atmosphere, and then atomized into powder at 1.0 MPa in an argon atmosphere using an inert gas atomization powdering process. After cooling, the powder is collected in stages, and 5-15 μm powder is obtained to obtain brazing powder. When weighing potassium fluoride, aluminum fluoride, and cesium fluoride, 0.5% of their respective weight should be added to compensate for volatilization losses during the smelting process; S3: Weigh 14.5% lithium chloride and 28% sodium chloride by mass ratio, melt them at 580℃ for 30 minutes in a nitrogen atmosphere, and then atomize them at 1.0MPa in a nitrogen atmosphere using an inert gas atomization powdering process. The resulting powder is cooled and sieved in a dry environment at room temperature and dew point ≤-40℃. Powder with a particle size of 45-75μm is collected to obtain mixed salt powder, which is then immediately vacuum-sealed. S4: Weigh out 50:44 of brazing powder and mixed salt powder by mass ratio and mix them. Spray the mixture into a composite solution containing 0.5% of the total mass of the mixture. Treat at 20 r / min for 10 min, then treat at 200℃ in a nitrogen atmosphere for 1 h. After cooling, the composite brazing powder is obtained. The composite solution is composed of polyethylene glycol and ethanol in a volume ratio of 1:8; S5: Mix the alloy powder and composite brazing powder at a dry weight ratio of 60:25 at 20 r / min for 30 min to obtain low melting point aluminum alloy flux-cored welding wire powder.

[0023] Example 3: This example provides a method for preparing low-melting-point aluminum alloy flux-cored welding wire powder, including the following steps: S1: Take 9.3% Si, 4.2% Cu, 0.2% Mg, 0.1% Bi, and 0.04% Sr by mass percentage, with the balance being Al. Melt at 750℃ and transfer to a sealed holding furnace. Atomize using an inert gas atomization process with argon as the atomization medium at 2.0 MPa. After atomization, cyclone classification is performed to collect powder of 45-150 μm to obtain alloy powder with oxygen content ≤0.2%. S2: Potassium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture A, and cesium fluoride and aluminum fluoride are compounded in a molar ratio of 1:1 to obtain mixture B. Mixture A and mixture B are combined at a mass ratio of 95:7 to obtain a combined material. The combined material is kept at 705℃ for 50 min in an argon atmosphere, and then atomized into powder at 2.0 MPa in an argon atmosphere using an inert gas atomization powdering process. After cooling, the powder is collected in stages, and 5-15 μm powder is obtained to obtain brazing powder. When weighing potassium fluoride, aluminum fluoride, and cesium fluoride, 1% of their respective weight should be added to compensate for volatilization losses during the smelting process; S3: Weigh 15.1% lithium chloride and 29.5% sodium chloride by mass ratio, heat to 611℃ for 42 min in a nitrogen atmosphere, and then atomize the powder using an inert gas atomization process at 2.0 MPa in a nitrogen atmosphere. The resulting powder is cooled and sieved in a dry environment at room temperature and dew point ≤ -40℃. Collect powder with a particle size of 45-75μm to obtain mixed salt powder, which is then immediately vacuum-sealed. S4: Weigh out 54:45 of brazing powder and mixed salt powder by mass ratio and mix them. Spray the mixture into a composite solution containing 2.0% of the total mass of the mixture. Treat at 40 r / min for 20 min, then treat at 300℃ in a nitrogen atmosphere for 3 h. After cooling, the composite brazing powder is obtained. The composite solution is composed of polyethylene glycol and ethanol in a volume ratio of 1:10; S5: Mix the alloy powder and composite brazing powder at a dry weight ratio of 72:31 at 50 r / min for 40 min to obtain low melting point aluminum alloy flux-cored welding wire powder.

[0024] Comparative Example 1: The difference between this comparative example and Example 3 is that in S5, the dry weight ratio of alloy powder to composite brazing powder is adjusted from 72:31 to 98:5, which significantly increases the proportion of alloy powder and reduces the proportion of flux components; the mixing speed and mixing time remain unchanged.

[0025] Comparative Example 2: The difference between this comparative example and Example 3 is that in S1, the Bi component was completely removed, and the original mass percentage of Bi was supplemented by Al element; the contents of Si, Cu, Mg, and Sr, the melting temperature, and the atomization and grading processes are all the same as in Example 3.

[0026] Comparative Example 3: The difference between this comparative example and Example 3 is that in S2, mixture B (cesium fluoride + aluminum fluoride eutectic system) is completely removed, and the combined material is 100% mixture A (potassium fluoride + aluminum fluoride, molar ratio 1:1). The remaining melting process, atomization parameters, and volatilization compensation rules remain unchanged.

[0027] Comparative Example 4: The difference between this comparative example and Example 3 is that in S3, the lithium chloride component is removed, and the original mass percentage of lithium chloride is completely replaced by sodium chloride, that is, the mixed salt is a pure sodium chloride system; the other requirements for melting temperature, atomization atmosphere and sieve particle size remain unchanged.

[0028] Experimental example; 1. The content (%) of oxygen that can be reduced by hydrogen in each group of metal powders was tested according to GB / T 4164-2008.

[0029] 2. The free flow time (s / 50g) of 50g powder in each group was tested according to GB / T 1482-2022.

[0030] 3. The loose bulk density (g / cm³) was tested according to GB / T 1479.1-2011 and GB / T 5162-2021. 3 ) and tap density (g / cm 3 ).

[0031] 4. Determine the melting temperature range (°C) according to JB / T 14409-2022.

[0032] 5. The tensile strength (MPa) and shear strength (MPa) of the joint shall be tested in accordance with GB / T 11363-2008. The base material shall be ER4047 aluminum alloy.

[0033] The results are shown in the table below:

[0034] As shown in the table above, the oxygen content in the examples was stably controlled at a low level of 0.12-0.16%, which is far superior to conventional water atomization processes; the loose packing density was 1.65-1.72 g / cm³. 3 Tap density: 1.89-1.98 g / cm³ 3 It exhibits good filling density; the outflow time is 25-29s / 50g, and its fluidity meets the process requirements for high-speed powder filling of flux-cored welding wire. The melting temperature range is only about 5℃, with high precision in melting point control and strong process stability. The melting temperature is maintained at around 480℃, thanks to the synergistic melting reduction of CsF-AlF3 hypoeutectic flux and Bi element. The overall melting temperature is about 70℃ lower than the traditional Nocolok flux system, demonstrating strong adaptability to low-temperature brazing. The joint tensile strength is 142-168MPa and the shear strength is 82-98MPa, indicating uniform brazing seam formation and dense interfacial bonding.

[0035] Comparative Example 1: After significantly reducing the flux ratio, the overall melting temperature increased by approximately 30°C, the low-temperature brazing characteristics weakened, the tensile strength decreased by 47.8% (157→82MPa), and the shear strength decreased by 50.5% (91→45MPa). The significant reduction in the low-melting flux ratio, coupled with the absence of the CsF-AlF3 component, resulted in a significant increase in the overall melting point. Simultaneously, insufficient flux failed to adequately remove the oxide film on the aluminum surface, leading to a sharp deterioration in the wettability of the brazing filler metal and a near halving of the joint's mechanical properties.

[0036] In Comparative Example 2, after complete removal of the Bi component, the melting temperature increased by 25℃ (478-483→503-508℃), the tensile strength decreased by 28.7% (157→112MPa), and the shear strength decreased by 31.9% (91→62MPa). The removal of Bi significantly increased the solidus line of the alloy; under the same brazing heat input, the liquid brazing filler metal spread area decreased, the wetting angle increased, the effective bonding area of ​​the joint decreased, and the mechanical properties significantly deteriorated.

[0037] In Comparative Example 3, after removing CsF-AlF3, the melting temperature surged by 72℃ (478-483→550-555℃), the advantages of low-temperature brazing disappeared, tensile strength decreased by 39.5% (157→95MPa), and shear strength decreased by 42.9% (91→52MPa). After replacing CsF-AlF3 with pure KF-AlF3, the flux melting point rose above 550℃, and the low-temperature brazing characteristics were completely lost. Insufficient flux deactivation led to a significant decrease in interfacial bonding quality and a marked deterioration in joint strength.

[0038] In Comparative Example 4, without lithium chloride and using a pure sodium chloride system, the tensile strength decreased by 22.9% (157→121 MPa) and the shear strength decreased by 26.4% (91→67 MPa). LiCl plays a role in reducing melting point and activating the chloride salt, while pure NaCl has a weakened ability to penetrate and remove the oxide film, resulting in a decrease in the bonding quality of the brazing interface and a significant degradation in mechanical properties.

[0039] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing low-melting-point aluminum alloy flux-cored welding wire powder, characterized in that, Includes the following steps: S1: The alloy powder is prepared by mass percentage of 7.5-12.5% ​​Si, 3.0-6.0% Cu, 0.1-0.5% Mg, 0.01-0.2% Bi, 0.01-0.05% Sr, with the balance being Al. After melting at 710-760℃, the alloy powder is prepared by inert gas atomization powder preparation process. S2: Potassium fluoride and aluminum fluoride are compounded to obtain mixture A, and cesium fluoride and aluminum fluoride are compounded to obtain mixture B. Mixture A and mixture B are combined at a mass ratio of 90-96:4-10 to obtain a combined material; the combined material is then atomized with inert gas to obtain brazing powder. S3: Weigh 14.5-16.5% lithium chloride and 28-31% sodium chloride by mass ratio, heat and melt them in a nitrogen atmosphere, and then atomize them with an inert gas to obtain mixed salt powder; S4: Weigh out 50-56:44-50 of brazing powder and mixed salt powder by mass ratio and mix them. Spray the mixture into the composite solution and stir. Then treat it in a nitrogen atmosphere at 200-350℃ for 1-3 hours. After cooling, the composite brazing powder is obtained. S5: Mix the alloy powder and composite brazing powder at a dry weight ratio of 60-75:25-40 to obtain low melting point aluminum alloy flux-cored welding wire powder. S2 specifically involves: mixing potassium fluoride and aluminum fluoride in a molar ratio of 1:1 to obtain mixture A; mixing cesium fluoride and aluminum fluoride in a molar ratio of 1:1 to obtain mixture B; combining mixture A and mixture B at a mass ratio of 90-96:4-10 to obtain a combined material; holding the combined material at 680-750℃ for 30-60 minutes in an argon atmosphere; then atomizing the material using an inert gas atomization process at 1.0-2.5MPa in an argon atmosphere; cooling and collecting the material in stages to obtain 5-15μm powder to obtain brazing powder. S3 specifically involves weighing 14.5-16.5% lithium chloride and 28-31% sodium chloride by mass ratio, melting them in a nitrogen atmosphere at 580-630℃ for 30-45 minutes, and then atomizing them using an inert gas atomization process at 1.0-2.5 MPa in a nitrogen atmosphere. The resulting powder is then cooled and sieved in a dry environment at room temperature and a dew point ≤-40℃, collecting powder with a particle size of 45-75 μm to obtain mixed salt powder, which is immediately vacuum-sealed.

2. The method for preparing low-melting-point aluminum alloy flux-cored welding wire powder according to claim 1, characterized in that, S1 is specifically composed of 7.5-12.5% ​​Si, 3.0-6.0% Cu, 0.1-0.5% Mg, 0.01-0.2% Bi, and 0.01-0.05% Sr by mass percentage, with the balance being Al. It is melted at 710-760℃ and transferred to a sealed holding furnace. It is then atomized using an inert gas atomization process with argon as the atomization medium at 1.5-3.0 MPa. After atomization, it is classified by cyclone and the powder of 45-150 μm is collected to obtain alloy powder.

3. The method for preparing low-melting-point aluminum alloy flux-cored welding wire powder according to claim 1, characterized in that, In S2, when weighing potassium fluoride, aluminum fluoride, and cesium fluoride, 0.5-2% of their respective weights are added to compensate for the volatilization loss during the smelting process.

4. The method for preparing low-melting-point aluminum alloy flux-cored welding wire powder according to claim 1, characterized in that, S4 is specifically prepared by weighing brazing powder and mixed salt powder in a mass ratio of 50-56:44-50 and mixing them, then spraying them into a composite solution containing 0.5-2.0% of the total mass of the mixture, stirring at 20-40 r / min for 10-30 min, and then treating them in a nitrogen atmosphere at 200-350℃ for 1-3 h, and obtaining composite brazing powder after cooling.

5. The method for preparing low-melting-point aluminum alloy flux-cored welding wire powder according to claim 1, characterized in that, In S4, the composite solution is composed of polyethylene glycol and ethanol in a volume ratio of 1:8-15.

6. The method for preparing low-melting-point aluminum alloy flux-cored welding wire powder according to claim 1, characterized in that, S5 specifically involves mixing alloy powder and composite brazing powder at a dry weight ratio of 60-75:25-40 at 20-60 r / min for 30-60 min to obtain low-melting-point aluminum alloy flux-cored welding wire powder.

7. A low-melting-point aluminum alloy flux-cored wire powder prepared by the method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Preparation for anhydrous magnesium chloride

    CN101279753A

  • Medium-temperature and corrosion-free aluminum brazing agent and preparation method thereof

    CN102717207A

  • Aluminum base welding wire

    CN105499831A

  • Brazing method of aluminum material and brazed structure

    US20150017470A1